Modulation Strategies for Indirect Matrix Converter: Complexity, Quality and Performance - Hendril Satrian Purnama; Tole Sutikno; Mochammad Facta (IAES Indonesia Section, 2018)
In general, there are two main classifications in matrix converters. The most common known type is conventional matrix converter (CMC) or direct matrix converter (DMC). The other type is indirect matrix converter (IMC). A brief review for modulation strategies are provided in this work for modulation strategies in IMC. There are several popular modulation methods for IMC such as carrier-based modulation and space vector modulation (SVM). A sinusoidal current waveform is produced on the input and output sides to implement the modulation method. In the conclusion the modulation methods will compared based on performance, theoretical complexity, and some other parameters.